Precocious Metamorphosis of Silkworm Larvae Infected by BmNPV in the Latter Half of the Fifth Instar - Xu, Ping-Zhen; Zhang, Mei-Rong; Wang, Xue-Yang; Wu, Yang-Chun (Frontiers in Physiology, 2021)
The mulberry silkworm (Bombyx mori) is a model organism, and BmNPV is a typical baculovirus. Together, these organisms form a useful model to investigate host–baculovirus interactions. Prothoracic glands (PGs) are also model organs, used to investigate the regulatory effect of synthetic ecdysone on insect growth and development. In this study, day-4 fifth instar silkworm larvae were infected with BmNPV. Wandering silkworms appeared in the infected groups 12 h earlier than in the control groups, and the ecdysone titer in infected larvae was significantly higher than that of the control larvae. We then used RNA sequencing (RNA-seq) to analyze silkworm PGs 48 h after BmNPV infection. We identified 15 differentially expressed genes (DEGs) that were classified as mainly being involved in metabolic processes and pathways. All 15 DEGs were expressed in the PGs, of which Novel01674, BmJing, and BmAryl were specifically expressed in the PGs. The transcripts of BmNGDN, BmTrypsin-1, BmACSS3, and BmJing were significantly increased, and BmPyd3, BmTitin, BmIGc2, Novel01674, and BmAryl were significantly decreased from 24 to 72 h in the PGs after BmNPV infection. The changes in the transcription of these nine genes were generally consistent with the transcriptome data. The upregulation of BmTrypsin-1 and BmACSS3 indicate that these DEGs may be involved in the maturation process in the latter half of the fifth instar of silkworm larvae. These findings further our understanding of silkworm larval development, the interaction between BmNPV infection and the host developmental response, and host–baculovirus interactions in general.